2011
DOI: 10.1016/j.scitotenv.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lower surface ocean pH upon the stability of shallow water carbonate sediments

Abstract: It is predicted that surface ocean pH will reach 7.9, possibly 7.8 by the end of this century due to increased carbon dioxide (CO(2)) in the atmosphere and in the surface ocean. While aragonite-rich sediments don't begin to dissolve until a threshold pH of ~7.8 is reached, dissolution from high-Mg calcites is evident with any drop in pH. Indeed, it is high-Mg calcite that dominates the reaction of carbonate sediments with increased CO(2), which undergoes a rapid neomorphism process to a more stable, low-Mg cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The presence of relatively high Mg concentrations may explain, in addition to their microcristalline structure, the low preservation potential of holococcoliths, which have very sporadic fossil records (Bown et al 2004). Differences in the Mg and Ca content of holo-and heteroccolithophores could also have consequences in relation to the increasing acidification of the world oceans (Orr et al 2005) because high-Mg calcite dissolves faster than low-Mg calcite after a drop in pH (Tynan and Opdyke 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of relatively high Mg concentrations may explain, in addition to their microcristalline structure, the low preservation potential of holococcoliths, which have very sporadic fossil records (Bown et al 2004). Differences in the Mg and Ca content of holo-and heteroccolithophores could also have consequences in relation to the increasing acidification of the world oceans (Orr et al 2005) because high-Mg calcite dissolves faster than low-Mg calcite after a drop in pH (Tynan and Opdyke 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The same may be true for dissolution arising as a result of bioerosion . In support of these predictions, experiments investigating the response of CaCO 3 sediments or substrates have shown convincing evidence of dissolution or increasing rates of dissolution as a result of increasing seawater CO 2 and acidity (Keir, 1980;Walter and Morse, 1985;Tribble and Mackenzie, 1998;Halley and Yates, 2000;Barnes and Cuff, 2000;Morse et al ., 2006;Andersson et al ., 2007;Tynan and Opdyke, 2011) . Similarly, coral blocks infested with communities of euendolithic and epilithic bioeroding organisms and exposed to seawater pCO 2 levels similar to those anticipated in the atmosphere by the end of the century (750 matm) dissolved at rates 48% higher than under control conditions (400 matm; Tribollet et al ., 2009) .…”
Section: Caco 3 Dissolution and Bioerosion On Coral Reefsmentioning
confidence: 99%
“…Later, Andersson and colleagues (Andersson et al, , 2005(Andersson et al, , 2007Morse et al, 2006) showed in a number of papers based on a numerical modeling approach that the global coastal ocean, as well as most shallow water environments in general, will not be significantly buffered by dissolution of carbonate minerals on time-scales of decades to hundreds of years. However, these authors have failed to convince skeptics as the issue is continuously being raised or mentioned in a number of forums and settings based on, for example, incorrect thermodynamic calculations (e.g., Loáiciga, 2006; see technical comment by Caldeira et al, 2007) (e.g., Tribollet et al, 2009;Hauck et al, 2011;Tynan and Opdyke, 2011). The first condition that requires recognition is that evidence of dissolution of CaCO 3 does not automatically mean that a significant buffer effect can be achieved.…”
Section: A J Andersson and F T Mackenzie: Revisiting Four Scientimentioning
confidence: 99%